1999
DOI: 10.1139/x99-009
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA as shared genetic markers among conifer species

Abstract: Polymerase chain reaction (PCR) primer pairs for 21 simple sequence repeat (SSR) loci in Pinus strobus L. and 6 in Pinus radiata D. Don. were evaluated to determine whether SSR marker amplification could be achieved in 10 other conifer species. Eighty percent of SSR primer pairs for (AC)n loci that were polymorphic in P. strobus also amplified SSR loci in two other soft pines of the subgenus Strobus but not in seven hard pines of the subgenus Pinus, nor in Picea glauca (Moench) Voss or Pseudotsuga menziesii (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 35 publications
3
43
0
Order By: Relevance
“…In pines, Echt et al (1999) successfully transferred 80% of the microsatellites tested within subgenus Strobus but only 29% among subgenus Strobus and Pinus, which diverged over 130 million years ago (approximately 13 million generations in pines) according to the fossil record (Miller 1977). Kutil and Williams (2001), using triplet-repeat microsatellites, found high transfer rates (100%) from P. taeda (subsection Australes) to a close relative of the same subsection, P. palustris but only moderate (and similar to our study) transfer success (47%) to P. halepensis (subsection Pinaster).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pines, Echt et al (1999) successfully transferred 80% of the microsatellites tested within subgenus Strobus but only 29% among subgenus Strobus and Pinus, which diverged over 130 million years ago (approximately 13 million generations in pines) according to the fossil record (Miller 1977). Kutil and Williams (2001), using triplet-repeat microsatellites, found high transfer rates (100%) from P. taeda (subsection Australes) to a close relative of the same subsection, P. palustris but only moderate (and similar to our study) transfer success (47%) to P. halepensis (subsection Pinaster).…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of methods have been developed to circumvent problems associated with repetitive DNA , the transfer of microsatellites between related conifer species is one of the more promising (Echt et al 1999;Kutil and Williams 2001;Shepherd et al 2002). Shepherd et al (2002) reported successful microsatellite transfer in hard pines (subgenus Pinus) for species that diverged a few million generations ago.…”
Section: Introductionmentioning
confidence: 99%
“…DNA sequences of the PCR primers for the loci examined in this study have been published elsewhere (Cato and Richardson, 1996;Echt et al, 1996;Vendramin et al, 1996). The PCR reaction and amplification conditions were as described by Echt et al (1996Echt et al ( , 1999. Fluorescently labeled amplified PCR products were separated by electrophoresis on a 41 cm polyacrylamide gel (Li-Cor model 4000L automatic DNA sequencer) (Li-Cor, Lincoln, NE, USA).…”
Section: Microsatellite Analysesmentioning
confidence: 99%
“…Other studies have considered cross-species amplification, with varying degrees of primer-sequence conservation being demonstrated in Pinus (Fisher et al 1998), Quercus (Steinkellner et al 1997), Populus (van der Schoot et al 2000 and among conifer species (Echt et al 1999).…”
Section: Transferability Of Microsatellite Markers In Eucalyptusmentioning
confidence: 99%